Thermal perception and willingness to walk among office workers in tropical low carbon city of Putrajaya, Malaysia - Kurmanbekova, Mainur (2020)
Majority of the city dwellers do not normally engage in regular physical activities due to their built environments that are designed to favour mobility by motor vehicles. For the last thirty years, the Malaysian population perpetrated high obesity rates due to decreased physical activity. Data from the Ministry of Health, Malaysia revealed that 73% of the total deaths recorded were due to Non-Communicable Diseases (NCDs), of which, approximately 35% comprised of the working population (< 60 years). Low Carbon City (LCC) is a concept of holistically minimizing carbon emissions in ways that do not compromise economic development and livability of the city. The Malaysian administrative capital—Putrajaya is among one of the designated Tropical Low Carbon City (TLCC) projects initiated by the government to reduce CO2 emission intensity. This study was conducted to investigate the physical inactivity among office workers through their perceived thermal hindrances on exposure to transient thermal conditions at three different building sites in Putrajaya. The multi-method research framework was applied combining the field measurements and cross-sectional survey approaches. Respondents suffering from NCD were identified and their level of awareness in pursuing active lifestyles was assessed. Perceived thermal hindrances that led to physical inactivity were measured by asking participants to rate their thermal sensation and thermal comfort votes at three different times of the working weekdays, namely morning (7:00-11:59 a.m.), afternoon (12:00-15:59 p.m.) and evening (16:00-18:30 p.m.). Structured observations using a walkability checklist were carried out to explore the features that decrease office workers’ willingness to walk in tropical climate. This study is among the first of its kind conducted in a TLCC. The findings may contribute to the National policy on Climate Change, particularly under the premises of societal well-being and environmental protection, as well as complement the LCC Framework. The results suggest that around 85% of the respondents in Putrajaya are vehicle dependent. Most of the respondents were willing to improve their health by walking more but expressed that the midday heat and the natural humidity of the tropical weather coupled with the lack of shaded paths were the main reasons for them to opt for motor vehicles as their mode of transportation in Putrajaya.